The Effect of Various Parameters on Measuring Alpha and Beta Particles from Soil Sample; An Environmental Dosimetry - Ahmad Esmaili Torshabi; Sepideh Mohammadzadeh (Frontiers in Biomedical Technologies)
Purpose: The measurement of natural radioactive decay in environmental samples such as soil has received increasing importance in recent years. Proportional counters in the form of large-area planar detectors are widely used for the initial screening of  radioactivity in environmental samples. In this study, the affecting factors in the alpha and beta particles emitted from natural radioactive soil sample was simulated using the Monte Carlo FLUKA code.